2023
DOI: 10.1371/journal.pcbi.1010994
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of spatial and phenotypic heterogeneity in an agent-based model of tumour-macrophage interactions

Abstract: We introduce a new spatial statistic, the weighted pair correlation function (wPCF). The wPCF extends the existing pair correlation function (PCF) and cross-PCF to describe spatial relationships between points marked with combinations of discrete and continuous labels. We validate its use through application to a new agent-based model (ABM) which simulates interactions between macrophages and tumour cells. These interactions are influenced by the spatial positions of the cells and by macrophage phenotype, a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…(2022) used an SABM to investigate the evolutionary rescue of drug‐resistant tumour subclones; Saha et al. (2023) used an SABM to investigate adaptive cancer therapy; and Bull and Byrne (2023) used an SABM to simulate interactions between macrophages and tumour cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) used an SABM to investigate the evolutionary rescue of drug‐resistant tumour subclones; Saha et al. (2023) used an SABM to investigate adaptive cancer therapy; and Bull and Byrne (2023) used an SABM to simulate interactions between macrophages and tumour cells.…”
Section: Introductionmentioning
confidence: 99%
“…Typical applications include understanding tumour development, inferring the effects of driver mutations, and predicting treatment outcomes. For example in recent studies, Aif et al (2022) used an SABM to investigate the evolutionary rescue of drug-resistant tumour subclones; Saha et al (2023) used an SABM to investigate adaptive cancer therapy; and Bull and Byrne (2023) used an SABM to simulate interactions between macrophages and tumour cells.…”
mentioning
confidence: 99%
“…Here, we emphasize that finding alternative indices for angle statistics to improve the data analysis of hexagonal versus tetragonal tile patterns is a timely research topic. Similar strategies for fitting parameters using summary statistics, pattern simplicity scores or persistent-homology approaches have been used to characterize pattern formation in several mathematical biology models, see [30, 31, 4, 3, 2, 26] for instance. Our study provides a mathematical basis for studying a wide range of tile patterns found in biological and non-biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…We analyze this behavior using angle summary statistics to discern among hexagonal and tetragonal like patterns. Similar strategies based on summary statistics have been used in pattern classification for different purposes in mathematical biology [30, 31, 3, 2].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of macrophages within the tumor conditions their polarization in relation to signals from the TME and interaction with other tumor and non-tumor cells. A new statistical function applied to an agent-based model (ABM), which takes into account the spatial distribution of macrophages within the tumor and the interaction with tumor cells, gives an idea of which macrophages should be targeted for re-education [ 127 ].…”
Section: Artificial Intelligence Can Help Re-education Of Tamsmentioning
confidence: 99%